Acupuncture and moxibustion in integrative oncology and new progress in China - Ming Yang; Yue Chen; Yuxiang Wan; Chen Shen; Jinchang Huang (Integrative Medicine Research)
Acupuncture and moxibustion are increasingly gaining recognition in the clinical and research fields of integrative oncology. This review synthesizes findings from clinical guidelines, systematic reviews, meta-analyses, and randomized controlled trials (RCTs) of acupuncture and moxibustion for cancer care. Clinical evidence highlights acupuncture’s efficacy in managing symptoms such as hot flashes, pain, insomnia, fatigue, and constipation. Acupuncture also demonstrates potential effects in reducing chemotherapy and radiotherapy-induced side effects. Recent advancements in China shows integrated therapies combining acupuncture with chemotherapy to enhance therapeutic outcomes. Additionally, laboratory studies reveal the potential of acupuncture and moxibustion to modulate the tumor microenvironment, boost chemotherapy efficacy, and strengthen immunity. Despite these promising results, there is a pressing need for well-designed trials and real-world studies to evaluate the long-term effects of standardized acupuncture and moxibustion treatments in cancer care.